0673 Increased Sympathetic and Decreased Parasympathetic Cardiac Tone In Patients With Obstructive Sleep Apnea And Periodic Limb Movements During Sleep. (27th April 2018) - Li, X; Ren, R; Zhang, Y; Zhou, J; Tan, L; Li, T; Tang, X
Abstract: Introduction: Approximately 24–27.6% patients with obstructive sleep apnea (OSA) may have periodic limb movements during sleep (PLMS). The association between OSA and cardiovascular has been well-established. However, the impact of PLMS alone even OSA+PLMS on the cardiovascular system of patients with OSA remains unknown. Heart rate variability (HRV) has been thought as an index reflecting autonomic system activity and may predict cardiovascular illness. The LF spectrum is mediated by both the sympathetic and parasympathetic systems, HF represents only parasympathetic activity. The current study compared HRV during N2 sleep stage in three patient groups and normal control. Methods: Eighty adult subjects were retrospectively identified and categorized into control group (n=20, AHI<5/h and PLMI≤15/h), PLMS alone group (n=20, AHI<5/h and PLMI>15/h), OSA alone group (n=20, AHI≥5/h and PLMI≤15/h), and OSA+PLMS group (n=20, AHI≥5/h and PLMI>15/h). All four groups were matched for age, sex and BMI. OSA+PLMS group and OSA alone group were also matched for AHI, OSA+PLMS group and PLMS alone group were also matched for PLMI. Time- and frequency-domain HRV measures were calculated during stable N2 sleep over 5-min periods. Results: The rankings in low frequency power (LF%) and normalized LF power (LFnu) are OSA+PLMS group>control group = PLMS = OSA, by comparison, for high frequency power (HF%) and normalized HF power (HFnu) the significant rankings are OSA+PLMS group<control = PLMS = OSA. For LF/HF ratio, significant rankings across groups were OSA+PLMS (0.68 ± 0.24)>control (0.43 ± 0.18) = PLMS (0.5 ± 0.26) = OSA (0.52 ± 0.21). Only in OSA+PLMS group, HFnu during N2 sleep showed significant negatively relationship with wakefulness time after sleep onset (r=-0.530, p=0.016), other three groups did not have such relationship. Conclusion: The OSA and PLMS patient exhibited an increased sympathetic activity and decreased parasympathetic activity, implying a possible additive effect of OSA and PLMS on HRV. Support (If Any): This work was supported by the National Natural Science Foundation of China (81530002, 81770087) and the National Basic Research Program of China (2015CB856406).